Behavior of Multi-Layer Composite Beams with Partial Interaction Part II - I. Aziz, Khalel; M. Ali, Zeyad; I. M. Al-Amery, Riyadh (Iraqi Journal of Civil Engineering, 2007)
ABSTRACT: In this study an attempt is made to derive governing equations satisfying equilibrium and compatibility, for multi-layer composite beams with different layers, materials properties and dimensions for linear material and shear connector behavior in which the slip (horizontal displacement) and uplift force (vertical displacement) are taken into consideration. The analysis led to a set of number differential equations containing derivatives of the fourth and third order, number of these equations depending on number of layers forming the beam section. The theory developed for three, four, and five layers. A general formula were derived to find the governing equations (compatibility and equilibrium equations) for any layered composite beam.